Hot Student Stories
top-5-grammar-and-spelling-checkers-to-rock-in-2019

Let g(x) be the reflection of f(x) = 3x + 2 in the x-axis. What is a function rule for g(x)? g(x) = 3x – 2 g(x) = –3x – 2 g(x) = 3x + 2 g(x) = –3x + 2

Ross Pratt

in Mathematics

follow
followin
1 answer
4 views

1 answer


Annie Barnes on January 15, 2018

Refrection of a function in the x-axis give the negative of that function.Refrection of f(x) = 3x + 2 on the x-axis gives -f(x) = -(3x + 2) = -3x - 2Therefore, g(x) = -3x - 2


Add you answer